PENYELESAIAN SENGKETA TANAH GRONDKAART MELALUI KONVERSI DEMI KEPASTIAN HUKUM DI INDONESIA - Putra Zein, Achmad Raditya; Ghibran Alhamda, Ismetullah Maulana (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2023)
Abstract The Grondkaart originated from the Dutch colonial era as proof of ownership, which is questionable because the revocation of the domein verklaring concept and its replacement with the concept of State Control automatically obscured the status of the Grondkaart land itself, resulting in differences of opinion between the community, judges, the government, and PT KAI. The research method used in this study is normative juridical through a legislative approach to identify legal gaps in the regulation of Grondkaart. Regulated in Government Regulation No. 8 of 1953 concerning State Land Control, Grondkaart is omitted from the provisions of the conversion of the Basic Agrarian Law (UUPA). Therefore, an application for land certification into Right of Use and/or Right of Management must be made as mandated by Article 49 (1) of Law No. 1 of 2004 concerning State Treasury in conjunction with Article 46 of Law No. 23 of 2007 concerning Railways. Keywords: Grondkaart, Disputes, Special Use Rights Abstrak Grondkaart berasal dari konsepsi jaman Belanda sebagai bukti kepemilikan menjadi patut dipertanyakan karena dari dicabutnya konsep domein verklaring menjadi konsep Hak Menguasai Negara secara otomatis mengaburkan kedudukan tanah Grondkaart itu sendiri, sehingga terdapat perbedaan pandangan antara masyarakat, Hakim, Pemerintah dan PT KAI. Metode Penelitian yang digunakan dalam melakukan penelitian ini adalah yuridis normatif melalui Pendekatan Perundang-Undangan untuk mengidentifikasi kekosongan hukum pengaturan Grondkaart. Diatur dalam PP No. 8 Tahun 1953 Tentang Penguasaan Tanah-Tanah Negara, Grondkaart luput dari ketentuan konversi UUPA. Sehingga harus dilakukan permohonan sertifikasi tanah menjadi Hak Pakai dan atau Hak Pengelolaan sebagaimana amanah Pasal 49 (1) Undang-Undang No. 1 Tahun 2004 Tentang Perbendaharaan Negara jo. Pasal 46 Undang-Undang No. 23 Tahun 2007 Tentang Perkeretaapian. Kata Kunci: Grondkaart, Sengketa, Hak Pakai